Passenger Requirements of a Public Transport Ticketing System - CAULFIELD, BRIAN; O'MAHONY, MARGARET (My University, 2005)
Currently in Dublin the system of public transport ticketing is under review and there are plans to introduce a multi-modal, multi-operator ticketing system. It is planned that this system would be operated via smart card technology, whereby passengers can pass between mode and operator with ease of use. The purpose of this paper is to examine what passengers require from their ticketing system with regard to the means and method of payment and the kind of information they require from an at-stop ticketing vending machine. Between January and February 2004 a detailed survey of a representative sample of 1,005 adults aged 15 and over in Dublin was completed using face-to-face at home interviews. With the format of the ticketing system decided upon (contact-less smart cards) the research focused upon the payment options and the design of the at-stop/station ticket vending machines. The first section of the paper looks at international examples of ticketing systems and how intelligent transport systems (ITS) applications have been used to aid passengers' comprehension of the ticketing system and ease of use of the system. The second section describes the methodology used in the data collection. The third section details the passenger requirements from a ticketing system based upon the data collected from the Dublin survey. The final section of the paper details the conclusions that can be drawn from the data gathered in the Dublin study.
IEEE ITSC 2005 IEEE
PUBLISHED
Vienna, Austria
Keywords: Public Transport; Smart & Sustainable Planet